Digitalization and green innovation of enterprises: Empirical evidence from China - Fan, Yaojun; Su, Quan; Wang, Xiaohong; Fan, Min (Frontiers in Environmental Science, 2023)
With the acceleration of the digital technology construction process, digitalization has given impetus to the transformation and upgrading of China's economy and micro businesses. China's social and economic sectors have begun to integrate and develop in-depth with digital technology. Whether the digitalization of enterprises can drive their green innovation is an urgent question to be explored. To investigate whether digitalization ultimately affects the green innovation of enterprises, this study, based on theoretical discussions, selected data from 2014 to 2019 for Chinese listed companies as a sample to empirically test the relationship between the two. Research has found that digitalization actually promotes green innovation in businesses. After the robustness test, the conclusion remains the same. In order to deepen the understanding of the impact of digitalization on the green innovation of enterprises, this study additionally analyzed the impact mechanism. Moreover, we find that the impact of digitalization on enterprise performance varies across scenarios. The findings of this study enrich the related theories of digitalization and sustainable development, and provide empirical evidence for the positive externalities of digitalization.